Performance, Heritability and Genetic Advance for Oil Yield and some Economical Characters in Oil Palm (Elaeis guineensis Jacquin) of Cameroon - Constantin, Mondjeli; Ridwani, Sobir; Syukur, Muhamad; Suwarno, and Willy Bayuardi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2017)
Knowledge of the magnitude of genetic variability, heritability and genetic advance in the selection of desirable characters could assist the plant breeders in ascertaining criteria to be used in the breeding programmes. Twenty three introgressed oil palm progenies were evaluated at the Specialized Centre for Oil Palm Research of Cameroon, from 2004 to 2014 to estimate performance, genetic variability, heritability and genetic advance of oil yield and some economic traits in terms to select new oil palm parent materials with the traits of interest. The results revealed high variability among oil palm population for all the characters. Moderate estimates of the phenotypic and genotypic coefficient of variations associated with high heritability and moderate genetic advance as percent of mean were obtained for characters of fresh fruit bunch, bunch number, oil yield, kernel to bunch, kernel to fruit, kernel yield and height increment. The results suggest the effectiveness of selection method for these traits and their improvement through their phenotypic performance. LM11087T x LM2749D and LM12960T x LM7409D were obtained as superior oil palm crossing parents with the potential production of 6.26 ton ha-1yr-1 of crude palm oil; they can be exploited in seed production and further breeding program.Keywords: genetic advance, heritability, introgressed progenies, oil yield, Phenotypic